HUBUNGAN KARAKTERISTIK, PENGETAHUAN DAN SIKAP PETANI TERHADAP PENGGUNAAN ALAT PELINDUNG DIRI SAAT MENYEMPROT PESTISIDA DI KEC.TIGA PANAH, KAB. KARO TAHUN 2022 - Masviona C Br Sinuhaji (2023)
Agriculture is a sector that has an important role in supporting the improvement of economic conditions in Indonesia. Farmers use pesticides in producing quality garden products, but one of the problems faced in the agricultural process implemented is the lack of public concern in using Personal Protective Equipment (PPE). This research used a cross-sectional study design. The purpose of this study was to analyze the relationship between respondents' characteristics, knowledge and attitudes towards the use of PPE in farmers. A total of 84 farmers in Tiga Panah District, Karo Regency were selected as samples in this study using purposive sampling technique. The data were analyzed using the Chi Square test. The results showed a significant relationship between education level (p-value 0.000), knowledge (p-value 0.000) and attitude (p-value 0.000) with the use of PPE. However, there was no significant relationship between age, gender, marital status and duration of work to the use of PPE. Therefore, workers are advised to use PPE completely, follow the programs provided and motivate each other in order to increase the use of PPE.